2014
DOI: 10.1097/ta.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of adding acute care nurse practitioners to a Level I trauma service with the goal of decreased length of stay and improved physician and nursing satisfaction

Abstract: Economic/decision study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 9 publications
(7 reference statements)
1
62
1
11
Order By: Relevance
“…4,7,8,23,[26][27][28][29][30] Significant reductions in hospital and intensive care unit LOS have been reported after the addition of PEs to surgical or trauma services. [7][8][9][10][11][12][13][14] Morbidity and mortality remain stable, and some studies have shown a reduction of in-hospital complication rates. An overall improvement in quality of care and continuity of care, as judged by health care workers, is a frequent theme in the studies we reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,7,8,23,[26][27][28][29][30] Significant reductions in hospital and intensive care unit LOS have been reported after the addition of PEs to surgical or trauma services. [7][8][9][10][11][12][13][14] Morbidity and mortality remain stable, and some studies have shown a reduction of in-hospital complication rates. An overall improvement in quality of care and continuity of care, as judged by health care workers, is a frequent theme in the studies we reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,14,15,21,23,27,30,31 It is important that we critically examine the effect that these changes have on the hospital work environment, and most importantly on patient care, before advocating widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many institutions are implementing alternative staffing models that include use of NPs and PAs to meet the needs of acute and critically ill patients, and recent reports highlight the benefit to providing quality of care in the ICU. [23][24][25][26][27][28][29] Additional research is needed to determine optimal NP or PA provider to patient ratios based on factors such as changes in patient acuity levels, need for invasive and therapeutic procedures, daily admission and discharge numbers, educational needs of patients and patients' families, and time spent by advanced practice providers in nonclinical duties. This research is especially important, because the roles of NPs and PAs are extending beyond general patient care management to include oversight of evidence-based practice initiatives and clinical staff education.…”
Section: Discussionmentioning
confidence: 99%